Posterior tibial plateau fracture: a new treatment-oriented classification and surgical management - Chen, Hong-Wei (Int J Clin Exp Med, 2015)
Purpose: To establish a classification system for the different types of posterior tibial plateau fractures (PTPF), and to explore the fracture patterns and early results of treatment. Methods: 39 PTPFs patients who received surgeries through posteromedial or (and) posterolateral knee approaches were analyzed retrospectively. Results: There were 5 types of PTPFs identified in the new classification system: posteromedial split fracture (type I, 7 patients), posterolateral split fracture (type II, 5 patients), posterolateral depression fracture (type III, 11 patients), posterolateral split and depression fracture (type IV, 2 patients), and posteromedial split combined with posterolateral depression fracture (type V, 14 patients). All patients underwent surgeries safely without complications. The average follow up was 18.1 months (12-30 months). The average weight-bearing durations were 15.6 weeks (12-20 weeks). Based on Rasmussen functional scoring system, 20 cases were regarded as excellent, 14 were good, 5 were fair, and 0 was poor. There was significant change in the Rasmussen functional score before (8.38 ± 2.87) and after surgery (24.20 ± 3.44). According to Rasmussen radiology system, 28 cases were excellent, 8 cases were good, 3 were fair, and none was poor. There was also a significant difference detected between pre-operation (6.77 ± 2.27) and post-operation (16.41 ± 2.65). Conclusion: This study presents a new classification system for the different types of PTPFs based on the treatment. The classification is clinically relevant and can be used to guide the surgical management.